2014
DOI: 10.1007/s10620-014-3421-y
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Gastrointestinal Fibrotic Stenosis in Crohn’s Disease

Abstract: Crohn's disease (CD) is a chronic inflammatory bowel disease that can involve virtually any part of the gastrointestinal tract. CD complications are the main indications for surgery. A large proportion of these interventions are due to stricturing disease. Although immunosuppressive treatments have been used more frequently during the last 25 years, there is no significant decrease in the need for surgery in patients with CD. Unfortunately, surgery is not curative, as the disease ultimately reoccurs in a subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 159 publications
0
32
0
1
Order By: Relevance
“…Pathologic bowel wall fibrosis is the result of aberrant healing secondary to recurrent bouts of intestinal inflammation and associated damage . The detection of bowel wall fibrosis is paramount, as areas of intestinal narrowing that are primary inflammatory may be sufficiently managed with medical (eg, anti‐inflammatory or immunosuppressive) therapy, whereas strictures containing considerable fibrosis require mechanical treatments, such as intestinal resection, stricturoplasty, or endoscopic balloon dilation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pathologic bowel wall fibrosis is the result of aberrant healing secondary to recurrent bouts of intestinal inflammation and associated damage . The detection of bowel wall fibrosis is paramount, as areas of intestinal narrowing that are primary inflammatory may be sufficiently managed with medical (eg, anti‐inflammatory or immunosuppressive) therapy, whereas strictures containing considerable fibrosis require mechanical treatments, such as intestinal resection, stricturoplasty, or endoscopic balloon dilation …”
mentioning
confidence: 99%
“…3 The detection of bowel wall fibrosis is paramount, as areas of intestinal narrowing that are primary inflammatory may be sufficiently managed with medical (eg, antiinflammatory or immunosuppressive) therapy, whereas strictures containing considerable fibrosis require mechanical treatments, such as intestinal resection, stricturoplasty, or endoscopic balloon dilation. 3,5 Unfortunately, the detection and measurement of intestinal fibrosis using conventional radiologic tests is difficult. A study by Adler et al 6 showed that whereas computed tomography can effectively detect active bowel wall inflammation, it performs suboptimally when trying to predict intestinal fibrosis.…”
mentioning
confidence: 99%
“…Some researchers suggested that the presence of ulcers, stricture site and length are the determinants of the success of the procedure. However, a systematic review of 353 strictures stated that the only predictor of a surgery‐free outcome was a short stricture . The same findings were supported by another review that included 3252 strictures in 1500 patients; those authors noted that steroid injection and increased length of stricture made earlier surgical re‐intervention more likely .
…”
Section: Small Bowel Surgery In Crohn's Diseasementioning
confidence: 99%
“…с использованием анти-цитокиновых препаратов, потребность в хирургиче-ском лечении при болезни Крона за последние 25 лет не уменьшилась [2]. До 50% пациентов с такой патологи-ей по крайней мере один раз в течение жизни нуждаются в операции по причине развившегося осложнения [3,4]. В то же время хирургические методы не гарантируют отсутствие обострений заболевания в будущем, и после оперативного этапа требуется обязательная противоре-цидивная терапия [5].…”
Section: вопросы современной педиатрииunclassified